Prevalence of neurological complications associated with Zika virus in a brazilian metropolis - Kattiucy Gabrielle da Silva Brito; Edarlan Barbosa dos Santos; Liliane dos Santos Maia Lucas; Marco Orsini; Rossano Fiorelli; Silmar Teixeira; Carla Ayres; Luan Correia; Victor Hugo Bastos; Eduardo Trajano; Carlos Eduardo Cardoso; Marcos R.G. de Freitas; et al. (MDPI AG, 2018)
The aim of this paper is to study the prevalence of Zika Virus (ZIKV) and the index of its neurological complications. This is a quantitative, cross-sectional epidemiological study. Data were collected through the compulsory notification of suspected ZIKV and its neurological alterations cases. 113 suspected ZIKV cases were reported, most of them in the summer, with a higher prevalence of females and in the fourth decade of life. Among the neurological changes, 15 Guillain-Barré Syndrome cases were reported, with one registered death. As neurological manifestations, most of them started 30 days after a ZIKV infection. No case has been confirmed laboratory. It is necessary to combat the vector, mainly in the summer, to reduce ZIKV infection and its neurological complications, besides instruction to the health professionals about these complications and serological tests requests for an accurate diagnosis.